FUNCTIONALITY AND PERFORMANCE STUDY OF IOT INTEGRATED MULTI-TANK WATER LEVEL MONITORING SYSTEM - N.Paramananthan, Nanthar Kugarn (IRC, 2020)
The purpose of this study is to develop an IoT system which will give accurate and live data which is stored and accessible to anyone around the world in the push of a button. For that very purpose, an experimental model was developed which consists of eight water tanks. The IoT system developed will be used to monitor the water level in each of the tanks and the flow rate into the tanks with the help of sensors and Raspberry Pi to connect the sensors to the Internet of Things. The Node-Red programming tool is used as it gives a very nice user interface which can be used to analyse the data. Three tests were done to calculate the mean percentage error of the data displayed. The three tests were for the initial water level, final water level and the flowrate of the water inlet. The error mean values of 20.835%, 10.5% and 10.145% were obtained respectively for the initial water level, final water level and the flowrate reading. This means the system is ‘Acceptable’ for the initial water level reading and ‘Good’ for the final water level and flowmeter reading based on the system performance evaluation developed.